Geochemistry and metagenomics analyses of bacterial community structure in selected waste dumpsites in Lagos Metropolis, Nigeria - Saibu, Salametu; Adebusoye, Sunday A.; Oyetibo, Ganiyu O.; Rodrigues, Debora F. (Frontiers in Environmental Science, 2023)
Dumpsites are reservoirs of persistent organic pollutants (POPs) and heavy metals (HMs), constituting environmental hazards to humanity. Autochthonous microorganisms in the dumpsites exhibit various degrees of responses to contaminants. Unfortunately, there is a dearth of information on types and concentration of pollutants and the array of microorganisms in these dumpsites which may play important roles in the metabolism of such pollutants or other community processes. Therefore, determining the microbial community structure in such contaminated sites across a municipality is essential for profiling the taxa that would serve as consensus degraders of the pollutants. In this study, soil samples from three dumpsites (Cele, CS; Solous, SS; Computer Village, CVS) were characterized for geochemical properties using GC-MS, MP-AES and other analytical protocols, while dynamics of bacterial communities were evaluated based on their 16S rRNA gene barcodes. A significant difference in bacterial community was observed among the dumpsites in relation to the extent of pollution with POPs and HMs. CVS, with the highest HMs contamination, was rich in Actinobacteria (41.7%) and Acidobacteria (10.2%), in contrast to CS and SS. Proteobacteria (34.1%) and Firmicutes (20%) were the dominant phyla in CS (highest POPs contamination), while Bacteroidetes (45.5%) and Proteobacteria (39.9%) dominated SS soil. Bacillus was the dominant genera in the most polluted site. Canonical correspondence analysis revealed that polyaromatic hydrocarbons (PAHs) and HM shaped the structure of the bacterial operational taxonomic units (OTUs) in the most polluted dumpsite. Out of total 706 OTUs, 628 OTUs exhibited significant correlation (>50%) with benzo(b)fluoranthene, azobenzene, dibenzofurans, pyrene, dibenzo(a,l)pyrene, Cu, and Zn. In particular, Proteobacteria (Achromobacter sp. and Serratia sp.), Bacteroidetes (Zhouia sp.), and Firmicutes (Bacillus sp.) were suggested to be pivotal to the ecophysiology of dumpsite soils contaminated with POPs and HMs. The results generally underscored the importance of metagenomic and physicochemical analyses of polluted systems in enabling correlations for useful prediction of drivers of such ecosystem. This will further improve the understanding of metabolic potential and adaptation of organisms in such systems.